Preparation of quantum dots from MoO3 nanosheets by UV irradiation and insight into morphology changes. Issue 48 (24th November 2016) - Lu, Xiaolong; Wang, Rongguo; Hao, Lifeng; Yang, Fan; Jiao, Weicheng; Zhang, Jian; Peng, Ping; Liu, Wenbo
Abstract : Remarkable morphology changes from MoO3 nanosheets to MoO3− x quantum dots upon UV irradiation and insight into the mechanism were reported. Abstract : After UV irradiation of orthorhombic molybdenum trioxide (α-MoO3 ) nanosheets dispersed in two different solvents including water/ethanol mixed solvents and individual N -methyl-2-pyrrolidinone (NMP), we observed remarkable but distinct morphology changes in combination with different photochromic phenomena. MoO3− x quantum dots (QDs) with both different sizes and oxygen vacancy concentrations could be acquired through this facile and efficient method. The consumption of photoexcited holes played an important role in the morphology changes. In water/ethanol, intercalation of H + originating from the oxidation of water by photoholes contributes to the acquisition of QDs. While in NMP, we provided a new insight and proved that photocorrosion induced by accumulated holes was responsible for the morphology evolution and acquisition of QDs.